Public-Key Authenticated Encryption with Keyword Search: A Generic Construction and Its Quantum-Resistant Instantiation. (8th September 2021) - Liu, Zi-Yuan; Tseng, Yi-Fan; Tso, Raylin; Mambo, Masahiro; Chen, Yu-Chi
Abstract: The industrial Internet of Things (IIoT) integrates sensors, instruments, equipment and industrial applications, enabling traditional industries to automate and intelligently process data. To reduce the cost and demand of required service equipment, IIoT relies on cloud computing to further process and store data. Public-key encryption with keyword search (PEKS) plays an important role, due to its search functionality, to ensure the privacy and confidentiality of the outsourced data and the maintenance of flexibility in the use of the data. Recently, Huang and Li proposed the 'public-key authenticated encryption with keyword search' (PAEKS) to avoid the insider keyword guessing attacks (IKGAs) in the previous PEKS schemes. However, all current PAEKS schemes are based on the discrete logarithm assumption and are therefore vulnerable to quantum attacks. In this study, we first introduce a generic PAEKS construction, with the assistance of a trusted authority, that enjoys the security against IKGA in the standard model, if all building blocks are secure under standard model. Based on the framework, we further propose a novel instantiation of quantum-resistant PAEKS that is based on NTRU assumption under random oracle. Compared with its state-of-the-art counterparts, the experiment result indicates that our instantiation is more efficient and secure.